2020
DOI: 10.1371/journal.pone.0240560
|View full text |Cite
|
Sign up to set email alerts
|

Early results of a low-profile stent-graft for thoracic endovascular aortic repair

Abstract: Purpose To assess outcomes of a low-profile thoracic stent-graft in the treatment of thoracic aortic pathologies. Methods A retrospective analysis of all consecutive patients with aortic thoracic pathologies treated with the RelayPro device in two university hospitals between October 2018 and July 2019. Results 23 patients (65% men; mean age 63.4 ± 15 years) were treated. Pathologies included aortic dissections (n = 10), 5 residual type A (22%) and 5 type B (22%), 6 degenerative aortic aneurysms (26%), 4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Four studies described RTAD as asymptomatic after TEVAR. Detailed description of the clinical presentation of RTAD is provided in Chassin-Trubert [76] [77] 2019 (2015-2018) France Paris SC 22 20 0 NR NR NR NR Jiechang Zhu [78] 2018 (2015-2016) China Tianjin SC 6.95 20 0 53 NR 16 NR Riesterer [79] 2018 (2002-2017) Germany Freiburg SC 16 34 1 NR NR NR NR Giles [12] 2019 (2005-2016) USA Gainesville SC 17 258 12 61.5 NR 203 NR Kuo [80] 2019 (2006-2016) USA Los Angeles SC 14 71 2 58.6 NR 52 NR Joo [81] 2019 South Korea Seoul SC NR 17 2 50.4 42 14 2 Cao [82] 2020 [83] 2020 (2018-2019) Germany Mainz, Tübingen NMC 11.6 5 0 NR NR NR NR Charltonouw [84] 2018 (1999-2014) USA Houston SC 51.6 43 3 NR NR NR NR Lou [85] 2020 (2012-2018) USA South Carolina SC 36 91 3 52.6 NR 60 NR Lee [86] 2020 Oshi [87] 2020 (2009-2019) Japan Fukuoka SC 39.2 40 1 66.5 NR 26 NR Puech-Leao [88] 2020 [89] 2020 [90] 2020 (2009-2018) China Shandong SC 10.7 79 1 49.9 NR 61 NR Bavaria [91] 2015 [92] 2018 (2007-2015) France Marseille SC 29 26 2 NR NR NR NR Ding [93] 2018 [95] 2016 [10] 2019 (2013-2017) China Zhejiang SC 25.8 571 12 NR NR NR NR Gao [8] 2019 diagnosed by CT at regular and irregular imaging follow-up period, respectively. According to Kruskal Wallis Test, cumulative incidence of RTAD did not statistically differ among the studies with regular or irregular imaging follow-up period (P = .63).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies described RTAD as asymptomatic after TEVAR. Detailed description of the clinical presentation of RTAD is provided in Chassin-Trubert [76] [77] 2019 (2015-2018) France Paris SC 22 20 0 NR NR NR NR Jiechang Zhu [78] 2018 (2015-2016) China Tianjin SC 6.95 20 0 53 NR 16 NR Riesterer [79] 2018 (2002-2017) Germany Freiburg SC 16 34 1 NR NR NR NR Giles [12] 2019 (2005-2016) USA Gainesville SC 17 258 12 61.5 NR 203 NR Kuo [80] 2019 (2006-2016) USA Los Angeles SC 14 71 2 58.6 NR 52 NR Joo [81] 2019 South Korea Seoul SC NR 17 2 50.4 42 14 2 Cao [82] 2020 [83] 2020 (2018-2019) Germany Mainz, Tübingen NMC 11.6 5 0 NR NR NR NR Charltonouw [84] 2018 (1999-2014) USA Houston SC 51.6 43 3 NR NR NR NR Lou [85] 2020 (2012-2018) USA South Carolina SC 36 91 3 52.6 NR 60 NR Lee [86] 2020 Oshi [87] 2020 (2009-2019) Japan Fukuoka SC 39.2 40 1 66.5 NR 26 NR Puech-Leao [88] 2020 [89] 2020 [90] 2020 (2009-2018) China Shandong SC 10.7 79 1 49.9 NR 61 NR Bavaria [91] 2015 [92] 2018 (2007-2015) France Marseille SC 29 26 2 NR NR NR NR Ding [93] 2018 [95] 2016 [10] 2019 (2013-2017) China Zhejiang SC 25.8 571 12 NR NR NR NR Gao [8] 2019 diagnosed by CT at regular and irregular imaging follow-up period, respectively. According to Kruskal Wallis Test, cumulative incidence of RTAD did not statistically differ among the studies with regular or irregular imaging follow-up period (P = .63).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 1963 potentially eligible articles. After considering our selection criteria, 78 eligible clinical studies [4,5,8,10,12,14,17,25–95] published between 2002 and 2020 were enrolled in the qualitative and quantitative analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among recent advancements in stent graft technology, LPSG might contribute to reducing embolization by less friction to the aortic wall during TEVAR compared with the CSSG. El Beyrouti et al [ 16 ] reported the early results of TEVAR using RELAY pro devices, of which the delivery sheath is designed 3- to 4-Fr smaller in outer diameter than the previous-generation devices of RELAY Plus. Their study revealed no thromboembolic complications, including endograft thrombosis, obstruction, stroke and SCI.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another repo1i of 13 PAU patients with persisting or recmTent, dissection-type, interscapular pain were treated with RelayPro with only one late type II endoleak that did not require additional treatment; there was no stroke or paraplegia, and no bleeding complication (including three patients undergoing prior percutaneous coronaiy intervention and receiving dual oral antiplatelet regimen).11 In a dual-center repo1i from Ge1many of 23 patients treated with RelayPro, pathologies included 5 residual type A dissection (22%) and 5 type B (22%), 6 degenerative ao1iic anemysms (26%), 4 penetrating ao1iic ulcers (17%), and ao1iic erosion, intramural hematoma and ao1iic rnpture (4% in each case). 12 Two cases (9%) were emergent and two urgent; proximal landing was in zones 0 (4%), 1 (4%), 2 (43%), and 3 (26%); five grafts were frozen elephant tiunk extensions.…”
Section: 5±501)mentioning
confidence: 97%